Rapid response to fifth-line brigatinib plus entrectinib in an ALK-rearranged lung adenocarcinoma with an acquired ETV6-NTRK3 fusion: a case report - Li, Dan; Zhu, Yue; Song, Jincheng; Yang, Dafu; Cui, Saiqiong; Liu, Xin; Wang, Le; Zhang, Jiangyan; Pan, Evenki; Dai, Zhaoxia (Frontiers in Oncology, 2024)
The management of non-small cell lung cancer (NSCLC), specifically targeting the anaplastic lymphoma kinase (ALK) with tyrosine kinase inhibitors (TKIs), is challenged by the emergence of therapeutic resistance. Resistance mechanisms to ALK TKIs can be broadly classified into ALK-dependent and ALK-independent pathways.Here, we present a case with lung adenocarcinoma (LUAD) harboring an ALK rearrangement. The patient had developed resistance to sequential ALK TKI therapies, with an acquired ETV6-NTRK3 (E4:N14) fusion as a potential mechanism of ALKindependent resistance to lorlatinib. Subsequently, the patient was treated with the combination of brigatinib plus entrectinib and demonstrated a positive response, achieving an 8-month progression-free survival. Our case provides a potential treatment option for LUAD patients with ALK rearrangements and highlights the utility of nextgeneration sequencing (NGS) in uncovering genetic alterations that can guide the selection of effective treatment strategies.